Incidence of haematopoietic malignancies in US radiologic technologists. Issue 12 (18th November 2005) - Linet, M S; Freedman, D M; Mohan, A K; Doody, M M; Ron, E; Mabuchi, K; Alexander, B H; Sigurdson, A; Hauptmann, M
Abstract : Background: There are limited data on risks of haematopoietic malignancies associated with protracted low-to-moderate dose radiation. Aims: To contribute the first incidence risk estimates for haematopoietic malignancies in relation to work history, procedures, practices, and protective measures in a large population of mostly female medical radiation workers. Methods: The investigators followed up 71 894 (77.9% female) US radiologic technologists, first certified during 1926–80, from completion of a baseline questionnaire (1983–89) to return of a second questionnaire (1994–98), diagnosis of a first cancer, death, or 31 August 1998 (731 306 person-years), whichever occurred first. Cox proportional hazards regression was used to compute risks. Results: Relative risks (RR) for leukaemias other than chronic lymphocytic leukaemia (non-CLL, 41 cases) were increased among technologists working five or more years before 1950 (RR = 6.6, 95% CI 1.0 to 41.9, based on seven cases) or holding patients 50 or more times for x ray examination (RR = 2.6, 95% CI 1.3 to 5.4). Risks of non-CLL leukaemias were not significantly related to the number of years subjects worked in more recent periods, the year or age first worked, the total years worked, specific procedures or equipment used, or personal radiotherapy. Working as a radiologic technologist was not significantly linked with risk of multiple myeloma (28 cases), non-Hodgkin's lymphoma (118 cases), Hodgkin's lymphoma (31 cases), or chronic lymphocytic leukaemia (23 cases). Conclusion: Similar to results for single acute dose and fractionated high dose radiation exposures, there was increased risk for non-CLL leukaemias decades after initial protracted radiation exposure that likely cumulated to low-to-moderate doses.